Giant Cell Glioblastoma; Long-Term Survival, and Correlation With Usual Glioblastoma - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2008)
Background: Giant cell glioblastoma (GCGB) is a rare tumor of the central nervous system and it accounts for only 1% of all intracranial tumors and 5% of glioblastomas. Objective: The aim of this study is to assess the histopathological and immunohistochemical findings and their correlation with survival time. Material-Method: We retrieved 23 consecutive GCGB specimens from a cohort of 650 glioblastoma cases and 24 usual glioblastoma cases with known survival information between 1995 and 2003. We used silver stain for reticulin framework, Ki-67, GFAP and CD45 as immunohistochemical stains. Results: GCGB accounts for 5% of all glioblastomas. The average survival is 31 and 16 months in GCGB and UGB respectively. There were significant differences between GCGB and UGB including the tumor infiltrating lymphocyte, perivascular lymphocyte, giant cell and oligodendroglia-like cells as histologic parameters. Presence of oligodendroglia-like cells was positively correlated with survival in GCGB. The parameters that were correlated with survival in UGB were younger age, high mitosis rate and a high Ki-67 proliferating index. Other parameters were not statistically significant in correlation with survival. Conclusion: GCGB had an overall longer survival rate than classical glioblastoma but the result was not statically significant.
Keywords: Giant cell glioblastoma; survival; immunohistochemistry; oligodendroglia-like cell; BRAIN-TUMORS; MULTIFORME; PATIENT; PROLIFERATION; MORPHOLOGY; GENOTYPE